The Effect of Bank Performance and Macroeconomics on the Profitability of Indonesian Sharia Commercial Banks - Sakinah Maulidah Mastniah Amin; Tiara Juliana Jaya (Al-Muamalat: Jurnal Ekonomi Syariah, 2024)
This study examines the relationship between the profitability of Islamic commercial banks with the functions of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Operating Expenses and Operating Income (BOPO), inflation, Gross Domestic Product (GDP), and interest rates. This quantitative study's monthly report of Islamic banking and the monthly report of statistical data for 2015-2022 are secondary data sources. A method used is called multiple linear regression analysis. Based on the results of research, CAR and NPF are significantly related to the profitability of Islamic commercial banks. In contrast, the results of BOPO, GDP, inflation, and interest rates have no significant relationship with Islamic commercial banks. ROA simultaneously affects CAR, NPF, BOPO, inflation, GDP, and interest rates. Based on the conclusions of this study. If Islamic banks want to maximize their profitability, they must maintain capital efficiency and stabilize non-performing financing and operational ratios.